The Weave of My Life: a Dissection of Dalit Existential Struggle and the Resistance through the Marxist Lens - Samim Bulbul Ahmed (JOELS: Journal of Election and Leadership, 2020)
Another name of life is existential struggle; so long man struggles either against adverse conditions or against their own selves for livelihood and common amenities to live on, so long they will survive. Continuous struggles—class struggle or struggle against nature or against social, religious, economic institutions-- bring radical changes in human life and usher in a revolutionary way of sustaining life. Dalit, working-people’s life is full of struggle and their ghetto is nasty, unhygienic, and under pressure of bourgeoisie and brahmanic dominance. In short, they are circumcised in respect of economic, social and religious perspectives and their hard-some struggle against all these, provide sustenance and life force to sustain their life in impervious backdrop. Marxism analyses the relationship of oppressed and oppressor from materialistic approach and tries to find out the real cause of suffering of the oppressed, proletariat people. Taking Marxism as tool of analysis, this research article tries to probe into deep the cause suffering of Dalit people and their struggle against oppressive institutions and mechanisms. At the same time, it delves into the very incipient point of being stigmatized as dalit, untouchable, low born, proletariat and speculates over the way of emancipation.